Ceci nest pas de lart: o conceito de reflexão em kant apropriado na recepção da arte contemporânea - Regina Sanches Xavier (2016)
This dissertation considers the experience of reflection presented in Kants work in many subjective aspects. Thus it aims to recognize in contemporary art debate the topicality of the feelings of reflection, which consists in one of the most puzzling notions proposed by Kant. Initially we have made the following questions: how the concept of reflection appears in The Critique of Judgment? Is it possible to submit the contemporary art to a dialogue with Kant´s concept of reflection? Lastly, the required updating of Kantian aesthetics would bring some support to contemporary art? These questions were the starting point of this research, which the main goal consists of extending the concept of reflextion in The Critique of Judgment to the contemporary art production, identifying the conditions of possibility of an autonomous aesthetics. We conclude that both universalist thesis and power of reflection (Kant´s aesthetic fundamental concept) are not obsolete. At least, what we want to bring up for discussion answers that they enable us to a complete and authentic reception of the contemporary art.